Increase in interleukin-8 and soluble intercellular adhesion molecule-1 in bronchoalveolar lavage fluid from premature infants who develop chronic lung disease. Issue 2 (March 1995) - Kotecha, S.; Chan, B.; Azam, N.; Silverman, M.; Shaw, R. J.
Abstract : Interleukin-8 (IL-8), soluble intercellular adhesion molecule-1 (sICAM), elastase and neutrophils were assessed in bronchoalveolar lavage fluid from nine infants who developed chronic lung disease (CLD) after respiratory distress syndrome (RDS), seven who had recovered from RDS, and in four control infants. IL-8, sICAM, elastase and neutrophils in bronchoalveolar lavage fluid were increased in the CLD group, the differences being most pronounced at 10 days of age. When babies with and without CLD were compared at 10 days of age, bronchoalveolar lavage fluid from the babies with CLD had significantly increased IL-8 (114.0 vs 12.7 ng/ml), sICAM (19.0 vs 1.1 micrograms/ml), elastase (6.9 vs 0.9 micrograms/ml) and neutrophils (1.9 vs 0.4 x 10(9)/l). In serum the increased concentration of IL-8 observed at birth in the CLD (247 pg/ml) and RDS (192 pg/ml) groups decreased over three weeks to the concentrations observed in the controls (< 70 pg/ml). Persistent inflammation could be a major contributory factor in the development of CLD.